Apakah Narsisme dan Love of money Memicu Kecurangan Laporan Keuangan? - Kuang, Tan Ming; Agustinus, Andre; Cahyadi, Andreas; Purwati, Misma Adhytia (Owner : Riset dan Jurnal Akuntansi, 2024)
The financial statements that accurately represent the financial performance of an entity in a relevant and reliable manner are crucial for economic decision-makers. Therefore, financial reports should be free from misrepresentation, especially those intentionally committed with the aim of deceiving users. While research on fraud is a significant issue in the business and accounting context, studies connecting personality factors to financial statement fraud remain limited. This study aims to examine the direct and indirect impact of narcissistic personality traits on financial statement fraud, considering the role of love of money as a mediating variable. The research adopts a quantitative approach, collecting primary data through questionnaires distributed via social media platforms such as Instagram and WhatsApp, as well as direct invitations to respondents. The sample consists of 90 accounting students from various universities, primarily located in West Java, Indonesia. Data analysis is conducted using the SEM-PLS approach. The research findings indicate that individuals with narcissistic personality traits tend to be obsessed with money and engage in financial statement manipulation. However, the study did not find a significant impact of the love of money on financial statement fraud, and the role of the love of money as a mediating variable was not identified. These findings offer practical insights for accounting program managers to integrate individual character development, aiming to produce graduates with ethics and integrity. For the accounting profession and corporate management, these findings underscore the importance of considering individual factors in mitigating the risk of accounting fraud.